Pseudanthias tequila, a new species of anthiadine serranid from the Ogasawara and Mariana Islands - Gill, Anthony C.; Tea, Yi-Kai; Senou, Hiroshi (Zootaxa, 2017)
Pseudanthias tequila is described on the basis of two specimens from the Ogasawara Islands. It also is recorded from the Mariana Islands on the basis of colour photographs. The species belongs to a complex that includes P. randalli (Lubbock & Allen), P. pulcherrimus Heemstra & Randall, P. flavicauda Randall & Pyle, P. oumati Williams, Delrieu-Trottin & Planes, and a potentially new species from the Line Islands. Species within the complex are distinguished on the basis of male live colouration, morphometric details and gill-raker and scale counts. Colour photos of all five species are provided.